2021
DOI: 10.1002/jso.26423
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of primary mobile spine chordoma

Abstract: Background and Objectives Chordomas of the mobile spine (C1–L5) are rare malignant tumors. The purpose of this study was to review the outcome of surgical treatment for patients with primary mobile spine chordomas. Methods The oncologic outcomes and survival of 26 patients undergoing surgical resection for a primary mobile spine chordoma were assessed over a 25‐year period. The mean follow‐up was 12 ± 6 years. Results The 2‐, 5‐, and 10‐year disease‐free survivals were 95%, 61%, and 55%. The local recurrence‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Although the complication rates were similar between these groups, those undergoing nonsurgical management had a higher rate of new neurologic deficits, suggesting opting for surgical management may help prevent neurologic decline in exchange for surgically related complications. The overall complication rate of those undergoing surgical resection of their recurrent chordoma was similar to the complication rate we previously reported after chordoma resection in the primary setting (76% vs. 73%), 19 and no complications were seen in the two patients undergoing EA resection.…”
Section: Figuresupporting
confidence: 84%
See 3 more Smart Citations
“…Although the complication rates were similar between these groups, those undergoing nonsurgical management had a higher rate of new neurologic deficits, suggesting opting for surgical management may help prevent neurologic decline in exchange for surgically related complications. The overall complication rate of those undergoing surgical resection of their recurrent chordoma was similar to the complication rate we previously reported after chordoma resection in the primary setting (76% vs. 73%), 19 and no complications were seen in the two patients undergoing EA resection.…”
Section: Figuresupporting
confidence: 84%
“…3,4,6,17,18 Our group previously reported the outcomes of a focused series of primary mobile spine chordomas treated surgically. 19 This study demonstrated the…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…In comparison, a single-institution study of 26 primary mobile spine chordoma patients reported on specific survival data, finding patients with R0 vs. R1 resection trended toward improved overall survival at 2 years (100% vs. 87%), 5 years (67% vs. 59%), and 10 years (67% vs. 35%) and local recurrence‐free survival at 2 years (100% vs. 67%), 5 years (83% vs. 52%), and 10 years (83% vs. 35%). They found similar survival data with patients receiving adjuvant RT and a complication rate of 73% 39 .…”
Section: Clinical Presentation and Prognostic Factorsmentioning
confidence: 56%